Cephalotane-type C20 diterpenoids from Cephalotaxus fortunei var. alpina. Issue 45 (4th November 2022) - Ge, Zhan-Peng; Zhou, Bin; Zimbres, Flavia M.; Haney, Reagan S.; Liu, Qun-Fang; Wu, Yan; Cassera, Maria B.; Zhao, Jin-Xin; Yue, Jian-Min
Abstract : Seventeen new cephalotane-type diterpenoids were isolated from Cephalotaxus fortunei var. alpina . Compounds 14 and 15 contain an unusual 7-oxabicyclo[4.1.1]octane moiety. Abstract : Seventeen new cephalotane-type diterpenoids, fortalides A–Q (1–17 ), along with five known analogues, were isolated from the seeds of Cephalotaxus fortunei var. alpina . Their structures were determined by extensive spectroscopic methods, as well as electronic circular dichroism (ECD) and X-ray crystallographic data analyses. Some isolates exhibited unusual structural features that were first found in cephalotane-type diterpenoids, such as the occurrence of the 7-oxabicyclo[4.1.1]octane moiety in 14 and 15 and the cis -arrangement of 3-OH and Me-19 in 9 . Besides, the antiplasmodial activity of these compounds was evaluated in this study.